1996
DOI: 10.1183/09031936.96.09112335
|View full text |Cite
|
Sign up to set email alerts
|

Does long-term oxygen therapy affect quality of life in patients with chronic obstructive pulmonary disease and severe hypoxaemia?

Abstract: D Do oe es s l lo on ng g--t te er rm m o ox xy yg ge en n t th he er ra ap py y a af ff fe ec ct t q qu ua al li it ty y o of f l li if fe e i in n p pa at ti ie en nt ts s w wi it th h c ch hr ro on ni ic c o ob bs st tr ru uc ct ti iv ve e p pu ul lm mo on na ar ry y d di is se ea as se e a an nd d s se ev ve er re e h hy yp po ox x--a ae em mi ia a? ? ABSTRACT: Long-term oxygen therapy (LTOT) improves survival in patients with hypoxaemic chronic obstructive pulmonary disease (COPD), but previous studies us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 25 publications
1
32
0
4
Order By: Relevance
“…Applying a general health questionnaire, the Sickness Impact Profile, Heaton et al (21) found no improvement in the quality of life of hypoxemic COPD patients after six months of LTOT delivered by either stationary or portable oxygen delivery systems. Okubadejo et al, (8) using SGRQ, also detected no change in the quality of life of patients with severe COPD receiving oxygen therapy through oxygen concentrators for 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying a general health questionnaire, the Sickness Impact Profile, Heaton et al (21) found no improvement in the quality of life of hypoxemic COPD patients after six months of LTOT delivered by either stationary or portable oxygen delivery systems. Okubadejo et al, (8) using SGRQ, also detected no change in the quality of life of patients with severe COPD receiving oxygen therapy through oxygen concentrators for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…(7,8) However, the correlation between HRQoL and arterial oxygenation is controversial in the literature. Previous studies using general health questionnaires have shown no correlations between PaO 2 and qualityof-life measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the St. George9s Respiratory Questionnaire (SGRQ) has become one of the most widely used instruments for assessing HRQL in respiratory patients, and has been translated into several languages [1][2][3]. The SGRQ has been used extensively in descriptive [4][5][6][7][8][9] and therapeutic evaluation studies (bronchodilator agents [10], oxygen therapy [11], psychotherapy [12] and respiratory rehabilitation [13]). However, this wide use is restricted mainly to the research setting.…”
mentioning
confidence: 99%
“…Although indications for LTOT are largely based on mortality data, some prior studies have also suggested improvements in other outcome measures, including depression, cognitive function, quality of life, exercise capability, and frequency of hospitalizations (19)(20)(21)(22)(23)(24)(25)(26)(27). The possibility of functional and clinical improvements in patients with COPD provides an additional, important motivation for the use of LTOT.…”
mentioning
confidence: 99%